2007
DOI: 10.1289/ehp.10325
|View full text |Cite
|
Sign up to set email alerts
|

HLA-B*1301 as a Biomarker for Genetic Susceptibility to Hypersensitivity Dermatitis Induced by Trichloroethylene among Workers in China

Abstract: BackgroundTrichloroethylene (TCE) is used extensively as an industrial solvent and has been recognized as one of the major environmental pollutants. To date, > 200 cases of TCE-induced hypersensitivity dermatitis among exposed workers have been reported worldwide, and TCE exposure has become one of the critical occupational health issues in Asia.ObjectivesThe study aimed to identify genetic susceptible biomarkers associated with the TCE-induced hypersensitivity dermatitis in genes located in the human leukocyt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
38
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 69 publications
(42 citation statements)
references
References 24 publications
4
38
0
Order By: Relevance
“…Recently, human leukocyte antigen (HLA)-B*1301 was identified as a marker of individual susceptibility to TCE-induced HS, with an odds ratio of 27.5 in a patient group in China. 28 This finding is analogous to that in carbamazepine-induced Stevens-Johnson syndrome and allopurinol-induced severe cutaneous adverse reactions, including DIHS, which have strong associations with HLA-B*1502 and HLA-B*5801, respectively. 29,30 In China, the allele frequency of HLA-B*1301 is higher in the southern population (10%) than in the northern population (3-4%), and this is may be a major factor explaining the mass outbreak of TCE-induced hypersensitivity dermatitis in the southern population.…”
Section: Genetic Factorssupporting
confidence: 59%
See 2 more Smart Citations
“…Recently, human leukocyte antigen (HLA)-B*1301 was identified as a marker of individual susceptibility to TCE-induced HS, with an odds ratio of 27.5 in a patient group in China. 28 This finding is analogous to that in carbamazepine-induced Stevens-Johnson syndrome and allopurinol-induced severe cutaneous adverse reactions, including DIHS, which have strong associations with HLA-B*1502 and HLA-B*5801, respectively. 29,30 In China, the allele frequency of HLA-B*1301 is higher in the southern population (10%) than in the northern population (3-4%), and this is may be a major factor explaining the mass outbreak of TCE-induced hypersensitivity dermatitis in the southern population.…”
Section: Genetic Factorssupporting
confidence: 59%
“…29,30 In China, the allele frequency of HLA-B*1301 is higher in the southern population (10%) than in the northern population (3-4%), and this is may be a major factor explaining the mass outbreak of TCE-induced hypersensitivity dermatitis in the southern population. 28 The allele frequency in Japan is 1.3%, 31 which is even lower than in the Han population in northern China and may partly explain why there have been fewer cases in Japan than in China. 7 Additionally, HLA-B*44 was demonstrated to be related to TCE-induced HS.…”
Section: Genetic Factorsmentioning
confidence: 95%
See 1 more Smart Citation
“…We have investigated the relation between polymorphisms of Tumor Necrosis Factor (TNF) and Interleukin (IL)-4 gene and the risk of TCE-induced hypersensitivity dermatitis, the results reveal that individuals with a heterozygous genotype of TNFα-308 were associated with the decreased risk of the disease relative to the homozygous genotype 18) . Li et al reported the Human Lymphocyte Antigen (HLA)-B*1301 is strongly associated with the disease among exposed workers and might be used as a biomarker to predict high risk individuals to TCE 19) . However, there is no study on the susceptible biomarkers in TCE metabolic process, which is as one of the basic biologic events in the development of TCE-induced hypersensitivity dermatitis.…”
mentioning
confidence: 99%
“…If a worker does not suffer from the disorders by the end of the 3rd month after the start of exposure, he/she is not susceptible. The incidence of the disorders in Guangdong Province is estimated to be less than 1 case per one hundred exposed workers 9) , and recently, human leukocyte antigen (HLA)-B*1301 and HLA-B*44 were identified as markers of individual susceptibility with an odds ratio of 36.8 in the patient group for having either of the HLA loci 15) . This is a finding analogous to carbamazepine-induced SJS/ TEN and allopurinol-induced severe cutaneous adverse reactions in which their strong associations with HLA-B*1502 16) and HLA-B*5801 17) , respectively, were reported.…”
mentioning
confidence: 99%